2002
DOI: 10.1099/0022-1317-83-12-2973
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of cellular immune responses to bovine herpesvirus-1 glycoprotein D by vaccination with CpG-enhanced plasmid vectors

Abstract: The potential of CpG-enhanced plasmid DNA vectors encoding a truncated secreted form of bovine herpesvirus-1 (BHV-1) glycoprotein D (tgD) to induce enhanced immune responses in cattle was investigated. We created tgD expression plasmids containing 0, 40 or 88 copies of the hexamer 5h GTCGTT 3h, a known pan-activating CpG motif in several species. The total tgD-specific IgG titre of calves immunized with these plasmids did not correlate with the CpG content of the plasmid backbone. However, the pBISIA88-tgD-vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 43 publications
5
41
2
Order By: Relevance
“…Despite their high BoHV-1 specific IFN-γ production and lymphocyte proliferation, the calves vaccinated three times with the pCDNA3.1VP8 showed no reduction of virus excretion as compared to the controls. This discrepancy between the cellular immune response and the virological protection after challenge contrasts with the results of studies performed with conventional vaccines [20,57] but is in agreement with observations of BoHV-1 DNA immunisation studies using other viral antigens [33,34,43]. The viral target antigens of DNA vaccines are very limited as compared to those encountered in conventional vaccines and the protective cellular immunity may be restricted to only a few proteins of BoHV-1.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Despite their high BoHV-1 specific IFN-γ production and lymphocyte proliferation, the calves vaccinated three times with the pCDNA3.1VP8 showed no reduction of virus excretion as compared to the controls. This discrepancy between the cellular immune response and the virological protection after challenge contrasts with the results of studies performed with conventional vaccines [20,57] but is in agreement with observations of BoHV-1 DNA immunisation studies using other viral antigens [33,34,43]. The viral target antigens of DNA vaccines are very limited as compared to those encountered in conventional vaccines and the protective cellular immunity may be restricted to only a few proteins of BoHV-1.…”
Section: Discussionsupporting
confidence: 81%
“…Although these DNA vaccines conferred an immune response comparable to that described by other groups [17,54], they induced weaker immune response and virological protection than the best protocol developed previously with conventional marker vaccine [20]. Therefore, a further experiment will aim at optimising some of the parameters known to modulate the efficacy of DNA vaccines such as the adjuvancy of immunostimulatory CpG motifs in the plasmid backbone [43]. Since the construct encoding truncated gD was associated with a high humoral immune response while pCDNA3.1VP8 induced a high cellular immune response an additional experiment will also test the efficacy of a vaccine simultaneously combining both constructs.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The BHV-1 VP22 full-length coding region was cut from pVP22-EYFP with the restriction enzymes BglII and BamHI and subcloned into the green fluorescent protein variant mammalian expression vector pEYFP-C1 (Clontech) to create pEYFP-VP22. Subsequently, the VP22 full-length coding region, including the stop codon, was cut from pEYFP-VP22 with BglII and HincII, blunted by the Klenow fragment of DNA polymerase I (Amersham Pharmacia Biotech), and inserted into the eukaryotic expression vector pMASIA (12,26), cut with EcoRI and blunted with the Klenow fragment of DNA polymerase I (Amersham Pharmacia Biotech), to create pMASIA-VP22.…”
Section: Cells and Virusmentioning
confidence: 99%
“…To confirm the subcellular localization of VP22 in the absence of other viral proteins, the UL49 gene was cloned into the eukaryotic expression vectors pMASIA (12,26) and pEYFP-N1, such that the UL49 gene is fused in-frame to the N terminus of the EYFP gene. Western blotting of COS-7 cells transfected with a plasmid encoding VP22-EYFP, EYFP, or VP22 demonstrated that BHV-1 VP22 had an apparent molecular mass of 35 kDa, as expected (16), whereas VP22-EYFP had an apparent molecular mass of 63 kDa, which corresponds to the combined apparent molecular masses of VP22 and EYFP (Fig.…”
Section: Subcellular Localization Of Vp22 and Vp22-eyfpmentioning
confidence: 99%